Study on Driving Performance of the Axial-Flow Blood Pump under the Condition of Large Gap - Yan Xu; Lizhi Cheng; Liang Liang (International Journal of Rotating Machinery)
The paper demonstrates an improvement of the simulation and computational methods for research on the system magnetic field and driving performance of the large gap magnetic drive system, which is used to drive the axial flow blood pump. The operational principle and structure of large gap magnetic drive system are narrated. Ansoft is adopted to simulate a three-dimensional driving torque to improve accuracy of computation. Experiments and theoretical study show that the use of Z10-T25 oriented silicon steel sheets as the electromagnetic core material can remarkably improve the system driving performance as well as optimize the volume and weight of the electromagnets. So the electromagnet made with oriented silicon steel sheets is conducive to improving the driving performance.